Validating a sentiment dictionary for German political language—a workbench note - Christian Rauh (Journal of Information Technology & Politics, 2018)
Automated sentiment scoring offers relevant empirical information for many political science applications. However, apart from English language resources, validated dictionaries are rare. This note introduces a German sentiment dictionary and assesses its performance against human intuition in parliamentary speeches, party manifestos, and media coverage. The tool published with this note is indeed able to discriminate positive and negative political language. But the validation exercises indicate that positive language is easier to detect than negative language, while the scores are numerically biased to zero. This warrants caution when interpreting sentiment scores as interval or even ratio scales in applied research.
doi:10.7910/DVN/BKBXWD
Keywords: 330; sentiment analysis; sentiment dictionary; text analysis; political language; German